2022
DOI: 10.3390/pathogens11050589
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Mucosa-Associated Microbiota and Its Impacts on Intestinal Health of Pigs Challenged with F18+ E. coli

Abstract: The objective of this study was to evaluate the significance of jejunal mucosa-associated microbiota and its impacts on the intestinal health of pigs challenged with F18+ Escherichia coli. Forty-four newly-weaned pigs were allotted to two treatments in a randomized complete block design with sex as blocks. Pigs were fed common diets for 28 d. At d 7 post-weaning, pigs were orally inoculated with saline solution or F18+ E. coli. At d 21 post-challenge, feces and blood were collected and pigs were euthanized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 54 publications
(106 reference statements)
1
44
1
Order By: Relevance
“…Enterotoxigenic E. coli is one of the most prominent bacteria responsible for post weaning diarrhea, which negatively impacts swine production. Previous studies demonstrated that enterotoxigenic E. coli attaches to glycoprotein receptors on enterocytes, produces enterotoxins including STa and STb, and induces the imbalance of microbiota in the intestine ( Fairbrother et al, 2005 ; Duarte and Kim, 2022 ), leading to immune system activation, diarrhea, and thus, growth retardation ( Sun and Kim, 2017 ; Duarte et al, 2020 ; Sun et al, 2021 ). In particular, nursery pigs are susceptible to the negative impacts of enterotoxigenic E. coli due to their immature intestinal development ( Moeser et al, 2007 ; Sun and Kim, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enterotoxigenic E. coli is one of the most prominent bacteria responsible for post weaning diarrhea, which negatively impacts swine production. Previous studies demonstrated that enterotoxigenic E. coli attaches to glycoprotein receptors on enterocytes, produces enterotoxins including STa and STb, and induces the imbalance of microbiota in the intestine ( Fairbrother et al, 2005 ; Duarte and Kim, 2022 ), leading to immune system activation, diarrhea, and thus, growth retardation ( Sun and Kim, 2017 ; Duarte et al, 2020 ; Sun et al, 2021 ). In particular, nursery pigs are susceptible to the negative impacts of enterotoxigenic E. coli due to their immature intestinal development ( Moeser et al, 2007 ; Sun and Kim, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae, a large family of Gram-negative bacteria found in the intestine of pigs, is considered opportunistic harmful bacteria and includes Escherichia, Klebsiella, Salmonella, Shigella, and Citrobacter spp, and thus Enterobacteriaceae have been connected to intestinal bowel diseases as these bacteria impaired intestinal barrier function and increase inflammation, oxidative stress, and crypt cell proliferation ( Baldelli et al, 2021 ). According to Duarte and Kim (2022) , enterotoxigenic E. coli challenge can also stimulate the overgrowth of Enterobacteriaceae, disrupting the balance of mucosa-associated microbiota in the intestine of pigs. The disrupted microbiota could be related to increased inflammatory response and oxidative stress ( Jang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A clear decrease in α-diversity following diarrheal events has been observed in human infants ( 59 ), and some authors have also observed decreased α-diversity in fecal microbiota of diarrheal piglets ( 58 ). However, other studies evaluating ETEC challenge effects on fecal microbiota have failed to observe significant differences in α-diversity ( 60 62 ). In agreement with our findings, Rhouma et al ( 63 ) reported reduced α-diversity in the fecal microbiota of pigs challenged with ETEC-F4, which was coincided with acute PWD symptoms, as opposed to other studies that only achieved subclinical states.…”
Section: Discussionmentioning
confidence: 97%
“…The enhanced growth performance observed in pigs fed phytobiotics in the current study could be associated with the reduction in the concentration of TNF-α in the jejunum and IgG in the jejunum and plasma of nursery and growing pigs. The jejunum accounts for critical functions in the immune system, in addition to the digestive role [ 4 , 21 ]. One proposed mechanism of phytobiotics affecting the immune system is through the modulation of intestinal microbiota, which in turn would reduce inflammatory response [ 17 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of protein was measured using a BCA protein assay (23225; Thermo Fisher Scientific, Waltham, MA, USA) following the instructions of the manufacturer. The concentration of protein was used to normalize the concentration of TNF-α, IgA, IgG, and PC [ 21 ].…”
Section: Methodsmentioning
confidence: 99%